Role of MDH2 pathogenic variant in pheochromocytoma and paraganglioma patients. (December 2018) - Calsina, Bruna; Currás-Freixes, Maria; Buffet, Alexandre; Pons, Tirso; Contreras, Laura; Letón, Rocío; Comino-Méndez, Iñaki; Remacha, Laura; Calatayud, María; Obispo, Berta; Martin, Antoine; Cohen, Regis; et al.
Abstract Purpose MDH2 (malate dehydrogenase 2) has recently been proposed as a novel potential pheochromocytoma/paraganglioma (PPGL) susceptibility gene, but its role in the disease has not been addressed. This study aimed to determine the prevalence ofMDH2 pathogenic variants among PPGL patients and determine the associated phenotype. Methods Eight hundred thirty patients with PPGLs, negative for the main PPGL driver genes, were included in the study. Interpretation of variants of unknown significance (VUS) was performed using an algorithm based on 20 computational predictions, by implementing cell-based enzymatic and immunofluorescence assays, and/or by using a molecular dynamics simulation approach. Results Five variants with potential involvement in pathogenicity were identified: three missense (p.Arg104Gly, p.Val160Met and p.Ala256Thr), one in-frame deletion (p.Lys314del), and a splice-site variant (c.429+1G>T). All were germline and those with available biochemical data, corresponded to noradrenergic PPGL. Conclusion This study suggests thatMDH2 pathogenic variants may play a role in PPGL susceptibility and that they might be responsible for less than 1% of PPGLs in patients without pathogenic variants in other major PPGL driver genes, a prevalence similar to the one recently described for other PPGL genes. However, more epidemiological data are needed to recommendMDH2 testing in patients negative for other major PPGL genes.